Anthropogenic Methane Emission and Its Partitioning for the Yangtze River Delta Region of China. Issue 5 (3rd May 2019) - Hu, Cheng; Griffis, Timothy J.; Liu, Shoudong; Xiao, Wei; Hu, Ning; Huang, Wenjing; Yang, Dong; Lee, Xuhui
Abstract: Urban areas are global methane (CH4 ) hotspots. Yet large uncertainties still remain for the CH4 budget of these domains. The Yangtze River Delta (YRD), China, is one of the world's most densely populated regions where a large number of cities are located. To estimate anthropogenic CH4 emissions in YRD, we conducted simultaneous atmospheric CH4 and CO2 mixing ratio measurements from June 2010 to April 2011. By combining these measurements with the Weather Research and Forecasting and Stochastic Time‐Inverted Lagrangian Transport models and a priori Emission Database for Global Atmospheric Research emission inventories, we applied three "top‐down" approaches to constrain anthropogenic CH4 emissions. These three approaches included multiplicative scaling factors, flux ratio, and scale factor Bayesian inversion. The posteriori CH4 flux density estimated from the three approaches showed high consistency and were 36.32 (±9.17), 35.66 (±2.92), and 36.03(±14.25) nmol·m −2 ·s −1, respectively, for the duration of the study period (November 2010 to April 2011). The total annual anthropogenic CH4 emission was 6.52(±1.59) Tg for the YRD region based on the average of these three approaches. Our emission estimates were 30.2(±17.6)%, 31.5 (±5.6)%, and 30.8 (±27.4)% lower than the a priori Emission Database for Global Atmospheric Research v432 emission inventory estimate. The scale factor Bayesian inversion results indicate that the overestimate was mainly caused by two source categories including fuel exploitation and agricultural soil emissions (rice cultivation). The posteriori flux densities for agricultural soil and fuel exploitation were 10.68 and 6.34 nmol·m −2 ·s −1, respectively, and were 47.8% and 29.2% lower than the a priori inventory. Agricultural soil was the largest source contribution and accounted for 29.6% of the YRD CH4 budget during the study period. Key Points: Agricultural soil was the largest source contribution and accounted for 29.6% of the YRD CH4 budget during our study period The overestimation was contributed by agricultural soils (rice cultivation) and fuel exploitation The emission estimates were 30.2(±17.6)%, 31.5%, and 30.8% lower than the a priori EDGAR v432 emission inventory estimate